Avaliação dos sistemas colinérgico e purinérgico em encéfalo de peixe-zebra (Danio rerio) adulto submetido a um modelo de hiperglicemia - Capiotti, Katiucia Marques (2015)
Diabetes Mellitus (DM) is a chronic disease that affects about 387 million people worldwide, being characterized as a heterogeneous group of metabolic disorders that have in common the symptom of hyperglycemia. The zebrafish (Danio rerio) has long been used in research to understand different diseases, due to characteristics shown by this species, as the genome and the description of the general organization and neuronal circuitry very similar to those observed in mammals and the presence of the main neurotransmitters, hormones, and receptors in this animal. Some metabolic disease models have already been developed using zebrafish, demonstrating that it is capable to reproduce important symptoms of human disorders. In this study, we characterized a hyperglycemia model in zebrafish and evaluated behavioral parameters and the effects on the purinergic and cholinergic systems under this condition. The hyperglycemia model was developed by immersion of adult zebrafish in 111 mM glucose for 14 days followed by 7 days of glucose washout. The protein glycation, the insulin sensitivity, the response to anti-diabetic drugs and the gene expression of insulin receptors and glucose transporters were evaluated. Our results showed that this model caused a rise in blood glucose levels, being able to reduce the response to insulin, increasing retinal protein glycation and the expression of mRNA levels of insulin receptors on skeletal muscle, in both groups of 111 mM glucose and after 7 days of glucose washout. Treatments with Glimepiride and Metformin were able to revert hyperglycemia. Studies have demonstrated that the cholinergic and purinergic systems are involved in the cognitive decrease mechanisms related to DM. The mnemonic capacity of the animals was assessed by inhibitory avoidance. Our results demonstrated that hyperglycemia was able to promote memory loss of the animals, which can be related to the increase of AChE activity. The therapy with galantamine, a AChE inhibitor, was able to reverse hiperglycemia-induced memory deficits. Our data also showed that hyperglycemia reduced the activity of hydrolysis of purine nucleotides (ATP, ADP and AMP) and increased the activity of adenosine deaminase (ADA), suggesting that these changes may be contributing to cognitive deterioration induced by DM. These findings may contribute to a better understanding of the signaling pathways involved in the cognitive impairment in DM and presenting alternative targets to the utilization of drugs that minimize the effects of hyperglycemia in the CNS.